Non-volant mammals of the Ibura National Forest, northeastern Brazil - Raone Beltrão-Mendes; Mônica Alves Cunha; Caroline Silva; Paulo Cezar Reys Bastos; Juan Ruiz-Esparza; Marcus Vinicius Brandão; Patrício Adriano da Rocha; Stephen Francis Ferrari (Acta Scientiarum. Biological Sciences, 2020)
Less than 10% of the original Atlantic Forest cover now remains standing in the Brazilian state of Sergipe, although few scientific studies have focused on its mammalian diversity. The present study describes the diversity of non-volant mammals found in the Ibura National Forest (INF), based on live trapping, and direct and indirect observations. We sampled the IBF on six days per month between June 2012 and August 2013, using live-traps (Sherman-type) positioned in pairs (ground and understory). We equally sampled semideciduous forest and an abandoned Eucalyptus plantation with dense understory (over 30 years). We also used non-systematics methods (direct observations, vestiges, camera-trap, and opportunistic captures). We recorded 18 species, from 12 families and 7 orders considering all the applied methods. Among recorded species, Bradypus torquatus and Lontra longicaudis are considered threatened of extinction. Considering only the live-trapping (totaling 3,240 trapping nights), we captured 125 individuals (3.85% success) from four species, Marmosa demerarae (52%), Didelphis albiventris (19.2%), Cerradomys vivoi (15.2%), and M. murina (13.6%). Estimated and observed richness was the same, suggesting a satisfactory effort. Didelphis albiventris and M. demerarae showed significantly higher captures in the dry seasons. Didelphis albiventris and C. vivoi showed significantly higher captures in the substratum, and M. demerarae higher in the understory. Cerradomys vivoi showed significantly higher captures in the Eucalyptus phytophysiognomy. Non-Metric Multidimensional Scaling and the ANOSIM showed a significant difference in the captured species among semidecidual forest and Eucalyptus. Despite the small area (144 ha), the INF still houses a relatively high mammalian diversity. Further investigations may help to understand the role of habitat reduction in the diversity and habitat partitioning among mammal species in the Atlantic Forest of Northeastern Brazil.